PERBEDAAN INFORMASI CITRA ANATOMI SEKUEN DIFFUSION WEIGHTED IMAGING (DWI) ANTARA PENGGUNAAN PROPELLER DENGAN TANPA PROPELLER PADA PEMERIKSAAN MRI BRAIN DENGAN KASUS STROKE - Yeti Kartikasari; M. Irwan Kartili; Dwi Rochmayanti; Nindya Aprilia (Poltekkes Kemenkes Semarang, 2020)
Background: Stroke is a brain disease where an acute nerve function is occurred due to the cerebral vascular disorders. To establish a diagnosis the stroke, it can be identified by employing the Diffusion Weighted Imaging (DWI) sequence in the MRI examination. Artifacts still exist on the MRI image which in turn reduce the resolution when using the DWI sequence. Adding the PROPELLER data acquisition method in the DWI sequence possibly improves the quality of brain images. The purpose of this study is to know the difference on the quality of anatomical image information between the DWI sequences with PROPELLER and without PROPELLER methods, and to determine adequate anatomical image appearance that created in amongst of the two methods, specifically for the stroke disease.Methods: this research is quantitative research with experimental approach. This study was conducted using MRI 1.5 T at Bethesda Hospital Yogyakarta. Data were 16 images from 8 patients using DWI sequences using PROPELLER without PROPELLER on MRI Brain examination with stroke. The results of the image were evaluated on 7 criteria: cortex cerebri, basal ganglia, thalamus, pons, cerebellum, stroke (infarction) and artifacts using questionnaires given to 3 respondents. Data analysis was done by Wilcoxon test to know the difference of anatomical image information on DWI sequence using PROPELLER without PROPELLER and to know better anatomical image information from both sequences seen from mean rank value.Results: The results shown, there is a significant difference on the quality of anatomical image information and the artifacts between the use of DWI sequence with and without PROPELLER methods ( 0.05). Based on the mean rank results, the DWI PROPELLER sequence has a higher mean rank value 4.50 compared to the DWI sequence without PROPELLER 0.00.Conclusions: The DWI PROPELLER sequence has better image results compared to the DWI sequence without PROPELLER.